Beyond the Law-Conscience Binary in Catholic Moral Thought - David Cloutier; Robert Koerpel (Journal of Moral Theology, 2021)
Amoris Laetitia invites Catholic moral theology to go beyond a law-conscience binary. In this essay, we offer a historical narrative of the law-conscience binary, showing in particular how its preoccupation with authority (whether of the Church's interpretation of the law or of the individual conscience) distracts from the central question of the good. Development of teaching becomes a jurisdictional battle, rather than a reflection and refinement of pursuing the good in the particular case. Constructively, we elaborate the suggestion of Cardinal Christoph Schonborn that Pope Francis instead offers a principles-prudence framework, and via a comparison with development of teaching on usury (a development prior to the law-conscience binary), we offer a possibility for how this framework might explain Amoris Laetitia's "target case."